Protected Endovascular Revascularization of Subacute and Chronic Total Occlusion of the Internal Carotid Artery - Shojima, M. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: The natural course of symptomatic carotid artery occlusion with hemodynamic impairment is poor. Surgical revascularization may improve the outcome; however, its efficacy has not been established yet. The goal of this study was to characterize the technical and clinical outcomes following endovascular recanalization of the ICA under cerebral circulatory protection. MATERIALS AND METHODS: Endovascular recanalization was attempted in 8 patients with symptomatic ICA occlusions. The duration of the occlusion ranged from 7 days to 7 months (mean, 2.5 months), and the mean length of the occlusion was 95 mm. Cerebral hemodynamics ipsilateral to the side of the occlusion were severely impaired in all patients. The endovascular procedure was performed under total cerebral circulatory protection, beginning with proximal protection with a subsequent switch to distal protection after successful guidewire passage. RESULTS: The occlusion was recanalized successfully in 7 of 8 patients (88%), resulting in improvement of ipsilateral cerebral hemodynamics without symptomatic stroke. Small asymptomatic ischemic lesions were detected in 6 of 8 patients (75%) on DWI, and 1 patient developed a mild groin hematoma. Ischemic episodes did not recur during the mean follow-up period of 19 months. However, 1 patient experienced asymptomatic reocclusion, which was re-treated successfully without complications, while another patient developed mild retinal hemorrhage at 3 months after the procedure due to the combination of antiplatelet and anticoagulant therapy. CONCLUSIONS: Endovascular revascularization of an ICA occlusion is feasible and well-tolerated in patients with subacute or chronic total occlusion of the ICA.